2019
DOI: 10.1111/jne.12807
|View full text |Cite
|
Sign up to set email alerts
|

Social creatures: Model animal systems for studying the neuroendocrine mechanisms of social behaviour

Abstract: The interaction of animals with conspecifics, termed social behaviour, has a major impact on the survival of many vertebrate species. Neuropeptide hormones modulate the underlying physiology that governs social interactions, and many findings concerning the neuroendocrine mechanisms of social behaviours have been extrapolated from animal models to humans. Neurones expressing neuropeptides show similar distribution patterns within the hypothalamic nucleus, even when evolutionarily distant species are compared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 138 publications
(167 reference statements)
0
21
0
Order By: Relevance
“…2 ). For most of these species, there is a full suite of genomic and molecular tools available that have allowed them to serve as model systems in social neuroscience [ 123 , 124 ]. Employing these species in studies on the effects of air pollutants on social behavior can serve as a bridge between reductionist laboratory experiments and field-based ecotoxicology assays [ 125 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 ). For most of these species, there is a full suite of genomic and molecular tools available that have allowed them to serve as model systems in social neuroscience [ 123 , 124 ]. Employing these species in studies on the effects of air pollutants on social behavior can serve as a bridge between reductionist laboratory experiments and field-based ecotoxicology assays [ 125 ].…”
Section: Resultsmentioning
confidence: 99%
“…Empathy‐related behaviours are assumed to be evolutionally originated from maternal care, and the involvement of oxytocin has been suggested 14,51‐53 . Postpartum females show caregiving behaviours toward their young, including pup retrieval, crouching, lactating and licking, 54 and it has been demonstrated that deficiency in the oxytocin receptor results in deficits in maternal behaviours, 29 suggesting the involvement of oxytocin in parental behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…OT and the closely related peptide hormone vasopression (VP) are among the oldest mammalian hormones and are considered to have been central to human evolution ( Robinson et al, 2019 ). Here, the description is restricted to OT (see, e.g., Carter, 2017 for a description of OT and VP dynamics).…”
Section: General Aspects Of Otmentioning
confidence: 99%